2021
DOI: 10.1089/heq.2021.0080
|View full text |Cite
|
Sign up to set email alerts
|

“We Are at The Forefront of Rural Areas” Emergency Nurse's Experience During Pandemic: A Qualitative Study

Abstract: Purpose: The pandemic makes everyone alert, including nurses who are in emergency rooms at community health centers, the importance of their experiences is a lesson for nurses to maintain themselves and be effectivein providing services. This study aimed to explore the experience of nurses who are in emergency rooms at rural area during the coronavirus disease pandemic. Methods: This qualitative research was conducted based on the Nvivo 12 analysis method using in-depth semis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
0
13
0
1
Order By: Relevance
“…35 This study also reported that nurses during the assessment found symptoms that they often complained about such as fever, nausea, vomiting, and coughing. 36 The CDC (2019) states that fever and cough are the most common symptoms that child Covid-19 patients often complain about, but other symptoms may arise such as nausea and vomiting that are not specific to COVID-19 symptoms. This requires accurate diagnostic tests.…”
Section: Discussionmentioning
confidence: 99%
“…35 This study also reported that nurses during the assessment found symptoms that they often complained about such as fever, nausea, vomiting, and coughing. 36 The CDC (2019) states that fever and cough are the most common symptoms that child Covid-19 patients often complain about, but other symptoms may arise such as nausea and vomiting that are not specific to COVID-19 symptoms. This requires accurate diagnostic tests.…”
Section: Discussionmentioning
confidence: 99%
“…One hundred and forty (22%) of the nurses reported that they had considered quitting their jobs. Nurses in Iran and Indonesia working with COVID-19 patients, expressed similar fears and concerns, including a shortage of PPE, and fear of the virus (Aditya et al, 2021;Moradi et al, 2021).…”
Section: Many Of the Early Studies Of Nurses And Covid-19 Came Frommentioning
confidence: 98%
“…The Indonesian nurses also expressed concern for their families who may be stigmatized themselves by the nurses' exposure to COVID-19 patients (Aditya et al, 2021).…”
Section: Many Of the Early Studies Of Nurses And Covid-19 Came Frommentioning
confidence: 99%
See 1 more Smart Citation
“…The face is associated with a person's identity because it can emphasize the importance of someone's individuality (Sohrabi et al 2020). However, in addition to being recognized as relevant individuals who experienced trauma, the nurses want to be recognized as members of their group or organization (Hopkinson & Jennings 2021, Aditya et al 2021.…”
Section: Follow-up Monitoring Of Post-disaster Assignmentmentioning
confidence: 99%